018 Lost in translation: documentation of on call neurology advice and the clinical impact of discrepancies. Issue 12 (14th November 2019) - Mahmood, Ammad; Davidson, Amy; Dani, Krishna
Abstract : Background: On-call neurology advice in the West of Scotland is centralised to one site handling 128±19 calls during working hours weekly. Telephone advice is documented at the regional centre by the neurologist and in patients' notes by the referrer. Errors in transcription can result in patient harm. Methods: Neurologists' documentation was compared retrospectively to patients' notes to identify discrepancies which were classified as major or minor based on potential for harm. Analysis was undertaken for one week in November 2016. A change in practice was implemented with all neurologists' documentation uploaded electronically to the patients' case record. The analysis was repeated in November 2018. Results: 53 cases were analysed before intervention and 63 afterwards. Post intervention the following improvements were seen: proportion of unsatisfactorily documented cases reduced from 21%→13% (undocumented cases increased 8%→13%, incomplete/inaccurate cases reduced 13%→0%); number of major and minor cases reduced (3→1 and 6→1 respectively); proportion of patients not receiving recommended treatment reduced from 20%→0%. The proportion of patients not undergoing recommended investigations increased from 10%→14%. Conclusion: In a regional service, neurologists documenting on-call advice in a manner accessible to all care providers led to reduced potential for patient harm, particularly in patients receiving recommended treatment.